Integrated freshwater prawn farming: State-of-the-art and future potential - Marques, Helcio L. A.; New, Michael B.; Boock, Marcello Villar; Barros, Helenice Pereira; Mallasen, Margarete; Valenti, Wagner C. [UNESP] (Taylor & Francis, 2016)
Integrated aquaculture can be defined as aquaculture systems sharing resources with other activities, commonly agricultural, agroindustrial, and infrastructural. Freshwater prawns are excellent options for integration, since they are omnivores and can therefore take advantage of a wide range of feed residuals, either from aquatic or terrestrial species. Furthermore, due to their benthic habit, they have a well-defined spatial distribution in the environment, thus favoring interaction with various species of fish, other animals, and even with plants. The integrated farming of freshwater prawns includes different culture systems, such as polyculture and coculture with other aquatic species, rice-prawn culture, hydroponics, and integration with terrestrial animals and plants. Our review includes a worldwide perspective on the main commercial integrated systems involving freshwater prawns, the present status of research on integrated freshwater prawn production and the main opportunities for integrated freshwater prawn farming in a world that is moving toward sustainability. The review continues by providing a brief summary of the future prospects for this form of aquaculture. Finally, we conclude that integrating freshwater prawn farming with other aquaculture and farming activities has considerable potential as a means of increasing food production in a sustainable fashion.
Keywords: Coculture; Freshwater prawns; IMTA; Integration; Macrobrachium; Polyculture; Potential